(untitled) (Research, Society and Development, 2021)
Objective: To identify in the literature the perception of the Primary Care nursing team regarding communication with patients with mental disorders. Methods: This is an integrative review, performed searches in electronic media, namely: LILACS, CINHAL, SciELO and PubMed. Studies from 2011 to 2021 were included, in the languages: English, Portuguese and Spanish, which corresponded to the theme of the nursing team’s perception regarding communication with patients with mental disorders. And experience reports and duplicate articles were excluded. Results: The search resulted in 07 articles that correspond to the theme of the review, of which were found in the LILACS (28.6%), CINHAL (28.6%), SciELO (28.6%) and PubMed databases (14,2%). Three categories were identified for content analysis: perception of the nursing team regarding the care of users with mental disorders, interpersonal relationships between nursing professionals and users with mental disorders, and communication as an important tool for providing care to users with mental disorders. Final considerations: It is observed that there are few studies that expose the perception of the nursing team regarding communication, and that there are barriers to providing care for people with mental disorders.